Spatially Defined Gene Delivery into Native Cells with the Red Light‐Controlled OptoAAV Technology. Issue 6 (7th June 2022) - Hörner, Maximilian; Weber, Wilfried
Abstract: The OptoAAV technology allows spatially defined delivery of transgenes into native target cells down to single‐cell resolution by the illumination with cell‐compatible and tissue‐penetrating red light. The system is based on an adeno‐associated viral (AAV) vector of serotype 2 with an engineered capsid (OptoAAV) and a photoreceptor‐containing adapter protein mediating the interaction of the OptoAAV with the surface of the target cell in response to low doses of red and far‐red light. In this article, we first provide detailed protocols for the production, purification, and analysis of the OptoAAV and the adapter protein. Afterward, we describe in detail the application of the OptoAAV system for the light‐controlled transduction of human cells with global and patterned illumination. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Production, purification, and analysis of PhyB‐DARPinEGFR adapter protein Basic Protocol 2 : Production, purification, and analysis of OptoAAV Basic Protocol 3 : Red light‐controlled viral transduction with the OptoAAV system Support Protocol : Spatially resolved transduction of two transgenes with the OptoAAV system